The Importance of The Form of Notarial Deed in The Shari'ah Banking Deed for Legal Protection for Customers (Muhil) Who Are Just in Indonesia - Subekti, Sri (CV. Publikasi Indonesia, 2024)
The development of economic business in Indonesia today, especially in the banking sector, is not only in the conventional field system but has spread to the realm of shari'ah system economic business. Indonesian citizens are predominantly Muslim, so it will increasingly attract market share to take part in the shari'ah economic business. The shari'ah banking system is a banking system that has not long been going on in Indonesia, so it is an excellent opportunity to give birth to various forms of problems in practice that then harm the customers as the primary consumers of shari'ah banks. The presence of a shari'ah notary is still needed in Indonesia because what is needed is the format of the Standard Agreement deed with its provisions focusing on the shari'ah economy so as to ensure legal certainty and public security in shari'ah transactions. This research uses a normative juridical approach, which will strengthen the theory of legal certainty, legal protection, expediency, and justice. Therefore, the conclusion obtained by the need for a shari'ah notary is significant.